2011
DOI: 10.1088/0953-8984/23/31/315403
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of layered cobaltites Y(Ba1 −xSrx)Co2O5 + δwithx= 0, 0.05 and 0.10

Abstract: The crystal structure and thermal expansion of Sr-doped layered cobaltites Y(Ba(1 - x)Sr(x))Co(2)O(5 + δ) (x = 0, 0.05 and 0.10) were studied by means of in situ neutron thermodiffraction in the temperature range 20 K ≤ T ≤ 570 K. The evolution with temperature of lattice parameters for the phases which crystallize in this system is presented, as well as their dependence on the oxygen non-stoichiometry δ. Each phase's volume has been fitted using available models based on the Grüneisen approximation to the zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…The study on samples substituted with Sr at the Basite confi rmed the phase-separation scenario [19,20]. We found that Sr addition destabilizes the ferrimagnetic SSO phase, as well as the "122" order, favoring instead a tetragonal and less ordered structure (Figure 3).…”
Section: Crystallography and Magnetism In Cobalt Oxidessupporting
confidence: 52%
“…The study on samples substituted with Sr at the Basite confi rmed the phase-separation scenario [19,20]. We found that Sr addition destabilizes the ferrimagnetic SSO phase, as well as the "122" order, favoring instead a tetragonal and less ordered structure (Figure 3).…”
Section: Crystallography and Magnetism In Cobalt Oxidessupporting
confidence: 52%